Abdominal Compartment Syndrome in Acute Pancreatitis: A Narrative Review - Narcis Octavian Zarnescu; Ioana Dumitrascu; Eugenia Claudia Zarnescu; Radu Costea (Diagnostics, 2022)
Abdominal compartment syndrome (ACS) represents a severe complication of acute pancreatitis (AP), resulting from an acute and sustained increase in abdominal pressure >20 mmHg, in association with new organ dysfunction. The harmful effect of high intra-abdominal pressure on regional and global perfusion results in significant multiple organ failure and is associated with increased morbidity and mortality. There are several deleterious consequences of elevated intra-abdominal pressure on end-organ function, including respiratory, cardiovascular, gastrointestinal, neurologic, and renal effects. It is estimated that about 15% of patients with severe AP develop intra-abdominal hypertension or ACS, with a mortality rate around 50%. The treatment of abdominal compartment syndrome in acute pancreatitis begins with medical intervention and percutaneous drainage, where possible. Abdominal compartment syndrome unresponsive to conservatory treatment requires immediate surgical decompression, along with vacuum-assisted closure therapy techniques, followed by early abdominal fascia closure.